Correspondence Again? Internal Realism and Truth - Pihlstrom, Sami (Problemos, 1998)
The paper deals with the relation between realism and (neo)pragmatism in the contemporary philosophy of science by investigating two rival positions: Ilkka Niiniluoto’s “critical scientific realism” and Hilary Putnam’s “internal realism”. The crucial difference between these two philosophers lies in their notions of truth. It turns out, however, that Putnam has, in his most recent writings, come closer to the kind of scientific realism he earlier abandoned as “metaphysical”. Many realistic critiques of his thought have, therefore, become rather irrelevant. Putnam’s pragmatic version of realism can even be seen as accommodating the traditional idea of correspondence truth, provided that this notion is liberated from all kinds of essentialism. The Putnamean pragmatist does not share Niiniluoto’s and other realists’ desire to “define” truth. What is extremely problematic in Putnam’s latest views, however, is his attempt to return to a pre- or nonphilosophical way of thinking about the relation between language and the world. His pragmatism is at least sometimes unpleasantly close to Rortyan antirepresentationalism.